The Performative Force of Cultural Products : Subject Positions and Desires Emerging From Engagement with the Manga Boys’ Love and Yaoi. - Lilja, Mona; Wasshede, Cathrin (My University, 2017)
This article deals with questions about the performative power of cultural products that travel the world. The Japanese manga genre Boys’ Love and Yaoi has gained a broad readership outside of Japan during recent decades. This has cultivated an image of Japan as sexually radical and ‘as more than Japan’, something which has produced alternative subject positions and practises regarding gender and sexuality among Swedish Boys’ Love/Yaoi followers. With the help of the concept hyperreality and elaborations on materiality within feminist theories, this article discusses: Which images of Japan and Sweden are produced as manga Boys’ Love/Yaoi – as cultural products – travel from Japan to Sweden? Which subject positions and forms of desires emerge? In order to understand how cultural products create new subjectivities, images and desires, we also ask: What can a sharper focus on materiality and the agency of matter add to the understanding of the concept of hyperreality and the construction of new realities? We argue that embodied experiences of certain subject positions and desires challenge the idea of the hyperreal as a surface phenomenon. Further, the article shows how the image of “Japan” is often coloured by the desires that West cultivates about the ‘other’.
Keywords: 306 Kultur und Institutionen; cultural products; Manga/Boys’ Love/Yaoi; subject positions; desires; hyperreality; materiality